KEPADATAN DAN POLA PERTUMBUHAN KERANG LOKAN (Geloina erosa, Solander 1786) DI EKOSISTEM MANGROVE BELAWAN - Hasan, Uswatul; Wahyuningsih, Hesti; Jumilawaty, Erni (Jurnal Perikanan dan Kelautan, 2014)
Density and growth pattern mangrove clam Geloina erosa (Solander 1786) inmangrove ecosystem Belawan, has been investigated in December 2013 - February2014. G erosa samples taken from three observation stations and each station observa-tions were made 3 replicates (months) sampling. The method used in determining thesampling point is the "purposive sampling". G. erosa samples were collected directlyby capturing by hand at the lowest tide. Result of the analysis data was the highestdensity of G. erosa at station 1 Nypah fruticants vegetation average of 3.207 individ-uals/m 2 , the lowest Heterogeneous vegetation at station 2 average of 1.362 individuals/m 2 . Allometric growth patterns show a pattern of negative (b <3).